1992
DOI: 10.1051/rnd:19920506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein kinase inhibitors on pig oocyte maturation in vitro

Abstract: porc / maturation des ovocytes / protéine kinase C / protéine kinase AMP! dépendante / calmoduline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In porcine oocytes, PKC was observed to participate in the regulation of the resumption of meiotic maturation (Jung et al, 1992;Coskun and Lin, 1995;Kim and Menino, 1995;Su et al, 1999;Shimada et al, 2001). Fan et al (2002b) demonstrated a change in the localization of PKC -α, -β I , -γ in maturing porcine oocytes and after their activation.…”
Section: Which Signalling Cascades Remained Silent In No-induced Oocymentioning
confidence: 99%
“…In porcine oocytes, PKC was observed to participate in the regulation of the resumption of meiotic maturation (Jung et al, 1992;Coskun and Lin, 1995;Kim and Menino, 1995;Su et al, 1999;Shimada et al, 2001). Fan et al (2002b) demonstrated a change in the localization of PKC -α, -β I , -γ in maturing porcine oocytes and after their activation.…”
Section: Which Signalling Cascades Remained Silent In No-induced Oocymentioning
confidence: 99%
“…(Jung et al, 1992 (Besterman and Schultz, 1990 (Besterman and Schultz, 1990). Mouse oocyte matu¬ ration is inhibited by genistein in a dose-dependent manner (ED50: 20 pg ml"1).…”
Section: Introductionmentioning
confidence: 99%
“…In other experiments, however, genistein failed to prevent EGF [33]-and IGF-I [38]induced cumulus expansion and oocyte maturation, suggesting that TK does not mediate growth factor effects on meiosis. Protein kinase C is probably not involved in this process [17,37].…”
Section: Introductionmentioning
confidence: 99%